Thinner Raw Material Supplier Recommendation System Using a Combination of AHP and TOPSIS Methods - Ananda Diar Eka Putra; Soffa Zahara; Yanuarini Nur Sukmaningtyas (Takaza Innovatix Labs Ltd., 2026)
The selection of thinner raw material suppliers at CV Tiga Jago needs to be done objectively because procurement decisions are not only influenced by price, but also quality, delivery, stock, payment, and service. This study aims to build a web-based Decision Support System to determine the criteria weights and generate the best supplier recommendations for each thinner raw material. The study uses a quantitative approach with the development of a web-based system through the stages of needs analysis, design, implementation, testing, and evaluation. Data were collected through observation, interviews, and documentation, then analyzed using the Analytical Hierarchy Process method for criteria weighting and the Technique for Order Preference by Similarity to Ideal Solution for supplier ranking. The AHP results show that quality has the highest weight of 0.3794, followed by price 0.2488, delivery 0.1604, stock 0.1024, payment 0.0655, and service 0.0434, with a Consistency Ratio of 0.0199. The TOPSIS results show that the best suppliers are different for each raw material. The system built is capable of managing data, performing AHP-TOPSIS calculations, displaying rankings, graphs, and reports, so that it can help the supplier selection process in a more measurable and documented manner